Reasons for non-participation in malformation scans in Denmark: a cohort study - Karina Hjort-Pedersen; Annette Wind Olesen; Ester Garne; Lene Sperling (BMC, 2018)
Abstract Background The aim of the study was to estimate the proportion of women giving birth in two hospitals in the Region of Southern Denmark who did not attend the malformation scan and to elucidate the reasons for not participating. Methods In this register-based descriptive study, we used patient administration systems to identify women who had given birth at two Danish hospitals between March 2013 and January 2015. We then linked this information with the hospital database for fetal medicine (Astraia) to identify women who did not attend the malformation scan at week 18-20. We reviewed the medical records of these women to validate the data and to identify the reason for non-participation. Results Of 7690 births, 153 (2%) women did not attend the malformation scan. The main reason for non-participation was a passive deselection (81%). Most of these women were not present in Denmark at the time of the malformation scan (61%) and few women declined (8%). Conclusions Less than 2% of a birth cohort in two major hospitals in Denmark did not attend the free offer of a malformation scan. Most of these women (81%) did not actively decide against the malformation scan. Very few (0.2%) declined the malformation scan. Non-attendance is not always due to an active decision made by the pregnant woman.